THE ROLE OF WAQF IN REBUILDING POST-COVID-19 SOCIETIES: A CASE STUDY APPROACH - Adamu Abubakar Muhammad; Shafaat Ahmad Aliyu; Adam Muhammad Ardo; Usman Jibril Mikail (YAYASAN CENDEKIA CITRA GEMILANG, 2025)
Global societies have been significantly influenced by the COVID-19 pandemic, which has increased socioeconomic disparities and put a tremendous burden on the social welfare, health, and educational systems. An effective tool for post-pandemic recovery and sustainable development in this setting is the Islamic endowment system known as Waqf. Using a case study methodology, this research investigates the function of Waqf in reconstructing post-COVID-19 society, emphasizing its use in tackling important issues including healthcare, educational reform, and poverty reduction. The paper illustrates how these institutions responded to the challenges of the pandemic and enhanced community resilience by examining effective Waqf models from different geographical areas. It also looks at how Waqf's influence may be increased in a world that is changing quickly through the use of novel financial structures, policy reform, and digital transformation. In order to assess Waqf's role in addressing post-COVID-19 societal challenges, the study uses a qualitative case study methodology, analyzing data from documented Waqf initiatives, stakeholder interviews, and secondary literature. The findings highlight the necessity of collaborative governance frameworks involving governments, religious institutions, and civil society in order to maximize Waqf's role in fostering equitable and sustainable post-pandemic recovery. Policymakers and stakeholders are given recommendations on how to incorporate Waqf into broader recovery strategies, making sure that it is in line with long-term development objectives and modern societal demands